‘Becoming Lina’: approaching the constitution of girlhood in a ‘post-socialist’ area through empiricist commitment - Blazek, Matej (Documents d'Anàlisi Geogràfica, 2011)
The paper addresses a gap in the literature on childhood and/in post-socialism and uses everydayness as the conceptual means that links both themes. It presents a story of Lina, a seven-year old Roma girl from a deprived urban neighbourhood in Bratislava, and maps everyday encounters, practices and recognitions that imply what matters in Lina’s life. The paper stresses importance of ungrounded empirical inquiry, and through identifying complex and heterogeneous associations in Lina’s life, it highlights acknowledgment of both broader social situations (such as post-socialism), but also mundane and often unremarkable moments in children’s lives. The notion of post-socialism is thus situated within the ‘descaled’ geographies of Lina’s everyday life, rather than as an imposing social condition.